IMPROVING THE QUALITY OF SMP ISLAM AL HAKIM SCHOOL THROUGH THE IMPLEMENTATION OF THE TEACHING CAMPUS PROGRAM - Mohamad Bastomi (Universitas Muhammadiyah Mataram, 2023)
3T (Disadvantaged, Outermost, and Frontier) areas experience difficulties in carrying out teaching and learning activities (KBM) such as not having adequate access to computer devices and smartphones, while teachers must be creative and adapt to technology in online learning. Al Hakim Islamic Junior High School is located in Rejotangan District, Tulungagung Regency. Al Hakim Islamic Junior High School was established in 2007, but until now it has not had its own building so it has to share with MI Miftahul Ulum. Some of the obstacles that arise in schools include the lack of facilities to support learning activities, low student interest in learning, backwardness in mastering technology, and so on. This community service program is carried out using socialization, education, mentoring, monitoring and evaluation methods. The Teaching Campus program has provided positive changes to the world of education in Indonesia, especially in schools with low National Computer-Based Assessment (ANBK) results. Good results can be achieved because literacy, numeracy, technology and administration programs are applied in the learning process. Kampus Mengajar is a sustainable program that can have a positive impact on schools such as increasing student motivation to learn, providing insight into learning methods and media for teachers, increasing reading culture, increasing student mastery of Microsoft basics, and improving school administration systems.